Hepatitis B Virus Genotyping Among Chronic Hepatitis B Individuals With Resistance to Lamivudine in Shahrekord, Iran - Karimi, Ali (Kowsar, 2014)
BACKGROUND: Hepatitis B infection, caused by hepatitis B Virus (HBV), is one of the major global public health problems. Hepatitis B Virus genotypes appear to show varying geographic distribution with possible pathogenic and therapeutic differences. Knowledge of HBV genotypes is very important for clinical treatment. Lamivudine is a nucleoside analogue that is clinically used to treat chronic hepatitis B infection. However, the main problem with the application of lamivudine is the development of viral resistance to the treatment with this anti viral drug. Besides, it has been suggested that lamivudine -resistant HBV may be genotype dependent. However, HBV genotype distribution and the biological relevance in this region are poorly understood. OBJECTIVES: The current study aimed to determine hepatitis B genotypes and their correlation with lamivudine- resistant HBV frequency among patients with chronic hepatitis B from Shahrekord, Iran. METHODS AND MATERIALS: Hepatitis B virus DNA was detected by conventional PCR in some of the serum samples obtained from HBsAg-positive Chronic Hepatitis B (CHB) patients who were referred to Health Centers of Shahrekord for routine monitoring of the disease. Subsequently, using real-time PCR, the DNA samples were used for genotyping and analysis of resistance to lamivudine. RESULTS: The DNA was detected in 23 out of 116 (19.82%) of the studied samples. Genotypes D and C were found in 17 out of 23 (73.9%), and in 6 out of 23 (26.1%) of the samples, respectively. To the authors’ best knowledge, the current study is the first report on isolation of Genotype C from Iran. Two out of 17 (11.76%), and 6 out of 6 (100%) of genotypes D and C were resistant to lamivudine, respectively. Resistance to this drug was significantly different between genotypes C and D (P <0.001). CONCLUSIONS: In addition to genotype D, other lamivudine resistant hepatitis B genotypes might be distributed in Iran.